Conjoint use of Naphthalene Diimide and Fullerene Derivatives to Generate Organic Semiconductors for n–type Organic Thin Film Transistors. Issue 4 (5th February 2021) - Birajdar, Shailesh S.; Brixi, Samantha; Rao, Pedada Srinivasa; Bhosale, Rajesh S.; Kobaisi, Mohammad Al; Gupta, Akhil; Lessard, Benoît H.; Bhosale, Sidhanath V.; Bhosale, Sheshanath V.
Abstract: In this paper, we described the design, synthesis, and characterization of two novel naphthalene diimide (NDI) core‐based targets modified with terminal fullerene (C60 ) yield – so called S4 and S5, in which NDI bearing 1 and 2 molecules of C60, respectively. The absorption, electrochemical and thin‐film transistor characteristics of the newly developed targets were investigated in detail. Both S4 and S5 displayed broad absorption in the 450–500 nm region, owing to the effect of conjugation due to fullerene functionalities. The electrochemical measurement suggested that the HOMO and the LUMO energy levels can be altered with the number of C60 units. Both S4 and S5 were employed as organic semiconductor materials in n‐channel transistors. The thin film transistor based on S4 exhibited superior electron mobility (μe) values ranging from 1.20×10 −4 to 3.58×10 −4  cm 2  V −1  s −1 with a current on‐off ratio varying from 10 2 to 10 3 in comparison with the performance of S5 based transistor, which exhibited μe ranging from 8.33×10 −5 to 2.03×10 −4  cm 2  V −1  s −1 depending on channel lengths. Abstract : Fullerene based transistor : Napthalene diimide(NDI)‐C60 (S4 ) and C60 −N−C60 (S5 ) based organic thin‐film transistors were fabricated via solution processing. The highest electron mobility values of 3.58×10 −4 and 2.03×10 −4  cm 2  V −1  s −1 were observed for S4 and S5, respectively, with a short channel length of 2.5 micron.